Pengaruh Ukuran Partikel Bentonit Alam Teraktivasi Pada Penurunan Limbah Cair Sarung Tenun Samarinda - Mustafa Mustafa; Marinda Rahim; Muh. Irwan; Desi Purnama Sari (Politeknik Negeri Samarinda, 2020)
One industry that needs attention is Samarinda's woven sarong business. This industry produces liquid waste that is produced from the coloring process using De Congo Red which is an organic dye. Discussing the business of Samarinda's woven sarong industry discharges its waste directly into the Mahakam River around the house or weaving location which will cause a harmful impact on the environment. The main process in this research is adsorption with active bentonite to determine differences in activated bentonite particles in the adsorption process. The performance of the adsorption process through the parameters of BOD, COD, TSS and, pH of the liquid waste. The adsorption process was carried out by mixing active bentonite and Samarinda waste woven gloves with 0.25 grams: 1 mL. The mixture is then stirred for 1 hour at a rotational speed of 468 rpm. The size of the active bentonite was varied by 210, 230, 270, 310, 330, 370 and 400 mesh. The results of this study have proven that active bentonite has 400 mesh more than the BOD, COD, TSS and pH values according to the standard requirements according to the Decree of the Governor of East Kalimantan No. 26/2002. Also involved were 34.5 mg / L, 64 mg / L, 168 mg / L and pH 8.